2005
DOI: 10.1177/153331750502000206
|View full text |Cite
|
Sign up to set email alerts
|

Memantine: Targeting glutamate excitotoxicity in Alzheimer's disease and other dementias

Abstract: The management of dementia has changed since the development of new antidementia drugs. The benefits observed in Alzheimer's disease (AD) with selective cholinergic transmission treatments are mainly symptomatic, without clear evidence of neuroprotection. The hypothesis that glutamate-mediated neurotoxicity is involved in the pathogenesis of AD is finding increasingly more acceptance in the scientific community. Glutamate receptors are overactive, and N-methyl-D-aspartate (NMDA) receptor antagonists have thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
63
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(63 citation statements)
references
References 48 publications
0
63
0
Order By: Relevance
“…Excitotoxicity is a major pathological mechanism underlying acute and delayed neuronal death induced by prolonged ischemia, traumatic brain and spinal cord injuries and Alzheimer's disease as well as epilepsy/seizure [19,25,43]. Therefore, studies have been focused on the reduction of glutamate accumulation in synaptic clefts and/or on the inhibition of glutamateinduced neuronal excitation for prevention of neuronal cell death under various neurological disease conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Excitotoxicity is a major pathological mechanism underlying acute and delayed neuronal death induced by prolonged ischemia, traumatic brain and spinal cord injuries and Alzheimer's disease as well as epilepsy/seizure [19,25,43]. Therefore, studies have been focused on the reduction of glutamate accumulation in synaptic clefts and/or on the inhibition of glutamateinduced neuronal excitation for prevention of neuronal cell death under various neurological disease conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Release and metabolism of AA through the phospholipase A 2 (PLA 2 )/ PTGS pathway is increased during excitotoxicity [12], a process that involves the over activation of brain excitatory neurotransmission. Kainic acid (KA), the prototypic excitotoxin, binds to the KA receptors in the brain and induces seizures that result in inflammation, oxidative damage and neuronal death, processes that have been implicated in neurological, neurodegenerative and psychiatric diseases [16,20,40,49,52,66,68,71,72]. Although it has been demonstrated that PTGS plays a role in excitotoxicity, the distinct role of the two PTGS isoforms has not been fully established.…”
Section: Introductionmentioning
confidence: 99%
“…Several cationic drugs, such as memantine, propranolol and clonidine, have recently been reported to exert a neuroprotective effect in the brain and retina, [18][19][20] and these reports support the substantial contribution of the study of cationic drug transport at the BRB in developing future treatments for retinal disease. In the in vivo transport study of verapamil in rats, the apparent influx clearance of [ 3 H] verapamil (K in, verapamil, retina ) was calculated to be 614 µL/(min·g retina), which was much greater than that of paracellular transport markers, 21) supporting the facilitative influx transport system The correlation of an initial uptake rate (log V) of compounds undergoing carrier-mediated transport (A) and passive diffusion (B) in TR-iBRB2 cells with the RUI in rats was studied, and a linear relationship described by Eqs.…”
Section: Cationic Drug Transport At the Brbmentioning
confidence: 83%
“…Because of the neuroprotective effects of cationic drugs, as previously reported, [18][19][20] the influx transport system of cationic drugs at the BRB is expected to be helpful in the delivery of neuroprotectants into the retina. Among such cationic neuroprotectants, propranolol reduces the expression of vascular endothelial growth factor (VEGF), and clonidine induces basic fibroblast growth factor (bFGF) to exert a neuroprotective effect.…”
Section: Cationic Drug Transport At the Brbmentioning
confidence: 99%